2009
DOI: 10.1073/pnas.0811357106
|View full text |Cite
|
Sign up to set email alerts
|

Signatures of natural selection are not uniform across genes of innate immune system, but purifying selection is the dominant signature

Abstract: We tested the opposing views concerning evolution of genes of the innate immune system that (i) being evolutionary ancient, the system may have been highly optimized by natural selection and therefore should be under purifying selection, and (ii) the system may be plastic and continuing to evolve under balancing selection. We have resequenced 12 important innate-immunity genes (CAMP, DEFA4, DEFA5, DEFA6, DEFB1, MBL2, and TLRs 1, 2, 4, 5, 6, and 9) in healthy volunteers (n ‫؍‬ 171) recruited from a region of In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
98
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(107 citation statements)
references
References 41 publications
8
98
0
1
Order By: Relevance
“…In a laboratory-based study with the insect Tribolium castaneum, Berenos et al (2011) demonstrated that evolution in the presence of parasites counteracted the effects of drift, leading to higher levels of allelic diversity within populations and lower levels of differentiation between populations. Although more diverged and in possession of an adaptive immune response, humans also show patterns in their innate immune genes that are similar to what we find here: while numerous single genes show signs of directional selection, innate immune genes have globally experienced stronger purifying selection than nonimmune genes (Mukherjee et al 2009;Deschamps et al 2016). Together, these results highlight that immune evolution is more complex than the outlier scenarios that garner the greatest attention in the literature.…”
Section: Discussionsupporting
confidence: 80%
“…In a laboratory-based study with the insect Tribolium castaneum, Berenos et al (2011) demonstrated that evolution in the presence of parasites counteracted the effects of drift, leading to higher levels of allelic diversity within populations and lower levels of differentiation between populations. Although more diverged and in possession of an adaptive immune response, humans also show patterns in their innate immune genes that are similar to what we find here: while numerous single genes show signs of directional selection, innate immune genes have globally experienced stronger purifying selection than nonimmune genes (Mukherjee et al 2009;Deschamps et al 2016). Together, these results highlight that immune evolution is more complex than the outlier scenarios that garner the greatest attention in the literature.…”
Section: Discussionsupporting
confidence: 80%
“…Furthermore, in a bottlenecked population of New Zealand robin (Petroica australis rakiura), seven out of nine analysed TLRs were polymorphic, with two to five amino acid variants each (Grueber et al, 2012). This relatively high genetic diversity observed in wildlife is in agreement with human studies (Mukherjee et al, 2009;Wlasiuk and Nachman, 2010), and shows that there is the potential for parasite-mediated selection to act on…”
Section: Resultssupporting
confidence: 72%
“…One plausible explanation for this is that strong purifying selection has constrained TLR10 within the B. t. taurus lineage. This explanation is supported by evidence that the vertebrate TLRs evolved under purifying selection (52,53), thereby preserving host ability to recognize specific PAMPs. Interestingly, TLR10 is the only functional member of the human TLR gene family for which a specific ligand has not been identified (16).…”
Section: Discussionmentioning
confidence: 94%